La lutte contre le réchauffement climatique en Chine, une nouvelle remise en question du « Consensus de Pékin » - Mylène Gaulard (Développement Durable et Territoires)
Since the beginning of the 2000s, the Beijing Consensus is referring to the central role of the State and of its economic policies in the current emergence of China, with a major place granted to the sustainable development and to the well-being of the population. The opposition to the liberal policies recommended by the international institutions, included in the term of Washington Consensus, is nevertheless widely overestimated by this analysis. Especially, the case of the fight against global warming in this country reveals that local authorities constitute significant obstacles to the effective application of the decisions taken by the government, thus calling into question the real capacity of the State to control the economy, to direct it on the chosen path.